ANALISIS PERILAKU IBU HAMIL DALAM DETEKSI DINI RISIKO TINGGI KEHAMILAN DENGAN INTEGRATED BEHAVIORAL MODEL DI KOTA BANJARMASIN - Fahriadi Ariady (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2016)
High risk pregnancy factors need to be considered since they could lead to obstetric complications which could lead to death of the pregnant woman. This study was a cross sectional study, with samples of 300 respondents of pregnant women in their trimesters in the city of Banjarmasin, using logistic regression analysis with 5% level of significance (α = 0.05).Analysis of the behavior of the mother in the early detection of high risk based on integrated behavioral models in the city of Banjarmasin, showed the following results: experiential attitude and instrumental attitude influenced the intention to perform the behavior, which could be in seen the p-value of the statistical tests carried out. For experiential attitude, the p = 0.000 (p <0.05) had the influence of 25 times or OR as many as 25.506. and instrumental attitude was at p = 0.000 (p <0.05), had the influence as much as 6 times or OR 6.769. Perceived norm had several elements: injuntivenorm, had an influence on the intention to perform the behavior, which could be seen from p = 0.000 (p <0.05) which meant that it had a significant influence and the influence was equal to 12 times (OR 12.364). Pregnant women in the early detection of high risk, was strongly influenced by the behavior of pregnant women themselves. So as to make that pregnant women have good behaviors, particularly in the early detection of high risk pregnancy, it is expected that to improve the ability of pregnant women, both with increased knowledge and skills through giving information to pregnant women concerning to early detection of high-risk pregnancies and with the health services provided.